The Analysis of a Short Story "Untuk Ibu": Microstructural Approach and Practice of Discourse - Dyah Kusumastuti (Journal of Languages and Language Teaching, 2020)
This paper aims to describe any cohesion to achieve coherence and the intrinsic elements of a short story titled "Untuk Ibu" (For Mother) by Kusuma Wijayanti on Annida magazine. Discourse analysis is done through the micro structural and the practice of discourse approach. The results of the discourse analysis of the short story titled "Untuk Ibu" meet all the other good grammatical aspects of cohesion as well as lexical aspect. The presences of grammatical and lexical cohesion build up the short story into a cohesive and coherent. From grammatical aspect, the short story has person references, comparative and demonstrative reference, substitution of clausal, ellipsis, causal conjunction, and conjunctions of time addition/additives.  While from the lexical aspect, it has reps anaphora and reps tautotes, synonyms of words and phrases with free morpheme synonym bound, antonyms type compound and opposition relations, collocation, hyponymy, and equivalency. The results of the analysis of the practice of discourse show that short story "Untuk Ibu" has the main theme of patience and compassion of a mother on her daughter. The main character is the mother and Ayu, some others characters are Mas Danu, Yu Yu, Supi, Mar, Parto Sopa and Lik Darmi. Plot is a mix that began with the exposure of problems in the form of regret the “I” (aku) figure against the behavior of naughty in opposition to the mother and then continued with the depiction of a cause of regret, and then ends with a meeting among the figures I (Ayu) and mother (advanced/progressive grooves). The background of the story majority happened at home (Madiun). In addition, this story has the first-person perspective I or Ayu and occurs in Javanese.